Non-twisted stacks of coated conductors for magnets: Analysis of inductance and AC losses. (September 2020) - Uglietti, Davide; Kang, Rui; Wesche, Rainer; Grilli, Francesco
Highlights: Many present HTS cable designs imitate twisted LTS cable designs. AC losses calculated by analytical methods but supported by experimental results. Main loss: hysteretic in twisted stacks, saturated coupling in non-twisted stacks. All magnets built with twisted or non-twisted tapes have similar large losses. Twisting a tape stack has modest effect on AC losses and inductance distribution. HTS magnet design should be based on rigorous physical analysis, not on imitation. Abstract: Almost all present High Temperature Superconducting (HTS) cable designs for magnets are based on twisted or transposed concepts that were developed for Low Temperature Superconducting (LTS) cables. However, requirements for LTS materials (like filament twisting) are in general not valid for HTS materials, which are extremely stable; for example, non-twisted multifilamentary Bi-2223 tapes have been successfully used in several magnets. Is twisting necessary for HTS cables? We investigated inductance mismatches and AC losses by numerical and analytical methods in twisted and non-twisted stacks of coated conductors; various experiments reported in the literature support the analysis. Large (hysteretic) losses are common in all magnets built with tapes and are far larger than in magnets built with LTS multifilamentary conductors, because of the aspect ratio and large width of the tape. In small magnets, losses and residual magnetisation could be reduced by replacing a wide tape with a non-twisted stack of narrow tapes. In large cables, we have found that twisting a stack of tapes reduces losses only marginally. Therefore, non-twisted stack cables could be designed to have losses comparable to those of twisted ones. Some examples of non-twisted large cables for fusion applications are discussed: non-twisted stack designs can be simpler, more robust and cost effective than twisted ones, but would require additional R&D.